Pemberdayaan Masyarakat melalui Pengembangan Paket Wisata Live-In Berbasis Kearifan Lokal - Tristanti, Tristanti; Sujarwo, Sujarwo; Santi, Fitta Ummaya (Jurnal Pengabdian Masyarakat (ABDIRA), 2025)
Empowerment is key to building a prosperous and independent community. The empowerment process cannot be separated from the active participation of the local community so that the program provides benefits back to the community. The objectives of this community service program are to provide knowledge to the target group regarding live-in tourism and to provide guiding skills to the target group in live-in tourism guiding. The methods used in this community service program are lectures, discussions, and hands-on practice. The target group of the program consists of 25 people who are members of the tourism awareness group (Pokdarwis). The training was conducted in Kampung Emas, Padukuhan Plumbungan, DIY. The outcomes of this community service program are: 1) the target group has awareness and knowledge about live-in tourism; 2) the target group has the skills to act as guides in live-in tourism.